Knowledge Management Maturity Assessment at Balai Besar POM in Serang - Akhmad Kurnia; Agung Wicaksono; Trikoranti Mustikawati (AIBPM Publisher, 2021)
Provincial Office of Indonesian Food and Drug Authority in Serang (BBPOM di Serang), its surveillance area in Banten Province, has cultivated knowledge sharing, including disseminating training results to implement Knowledge Management (KM). However, by evaluation in 2021, the number of knowledges shared in the KM portal is still low. These conditions need further investigation to identify their strengths and opportunities for improvement in implementing KM. This study aims to measure the Maturity of KM implementation at BBPOM di Serang. The methods used are quantitative measurement through surveys, qualitative through interviews, and desk studies. The survey was conducted using APO KM assessment tools to see the maturity gap of KM implementation. The surveys showed a score of 162.34 which means the application of KM is continuously evaluated and improved; the score is categorised as high because there are applicable business processes, namely the Implementation of Personnel Management, Management System, and Bureaucratic Reform. However, from the survey, interviews, and business processes examination, there are opportunities to improve the implementation of KM. Based on these opportunities, solutions are recommended to increase the Maturity of KM implementation.